Ars moriendi – gdy początek oznacza kres - Tokarczyk-Bar, Urszula (Kultura-Społeczeństwo-Edukacja, 2016)
Both the beginning and the end of human life are connected to many moral dilemmas. The discussion becomes especially emotional when we deal with the situation of parents (or sometimes just a mother) who decide about their baby’s life in its prenatal phase of development. The in vitro procedure itself still gives rise to a number of doubts in some circles. Especially the multiple embryo transfer exposes the mother to a potential stress of deciding about the further course of pregnancy. To be more precise: some patients are persuaded into selective abortion. Polish law allows abortion in three cases. Still, the act of 1997 does not seem to be precise enough. On the one hand there is a threat of it being abused, on the other – there are difficulties when it comes to it being executed. Due to the medical advancement issues that were obvious twenty years ago need to be newly evaluated (e.g. the age of an infant capable of surviving outside the mother’s womb is gradually decreasing). It also seems that it is necessary to look upon terms such as abortion, termination, lethal defects, overzealous therapy, abandoning overzealous therapy, euthanasia (active, passive), euthanasia attitude, hospice care attitude, chronic condition, terminal phase, terminal state, palliative care. It becomes crucial especially now when Poland is faced with projects of opposing legal acts: those delegalizing abortion completely and those allowing for complete freedom of it. Therefore, a sound bioethical discussion is in order, such that will allow for the optimal standpoint. At the same time it would be beneficial to concentrate on thanalogy education because, as distant and unrealistic those ultimate matter may seem now, they concern every human being.